1954
DOI: 10.1037/h0059180
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of psychological reports in a clinical setting.

Abstract: 2 The first book on writing clinical reports [1] was published as this manuscript was being prepared. 8 The project reported here was a cooperative one in which all staff members of the VA Mental Hygiene Clinic, Chicago, Illinois, participated. The authors wish to acknowledge this participation and to thank especially Drs. D. G. Wright, John G. Watkins, and Miss Clara Weimer for their aid in completing the project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1955
1955
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In their survey of psychiatrists' opinions of the usefulness of psychological assessment reports, Smyth and Reznikoff (1971) found that 23% of respondents cited stereotyped reporting as a limitation of most reports. Another study of psychologists, psychiatrists, and psychiatric social workers who were asked to rate the quality of psychological assessment reports at a Veterans Affairs hospital found that the most frequent complaint was a lack of individualized, behavioral description of the client (Garfield, Heine, & Leventhal, 1954). There is some empirical evidence that individualized reports help consumers address client problems.…”
Section: Relevance and Responsementioning
confidence: 99%
“…In their survey of psychiatrists' opinions of the usefulness of psychological assessment reports, Smyth and Reznikoff (1971) found that 23% of respondents cited stereotyped reporting as a limitation of most reports. Another study of psychologists, psychiatrists, and psychiatric social workers who were asked to rate the quality of psychological assessment reports at a Veterans Affairs hospital found that the most frequent complaint was a lack of individualized, behavioral description of the client (Garfield, Heine, & Leventhal, 1954). There is some empirical evidence that individualized reports help consumers address client problems.…”
Section: Relevance and Responsementioning
confidence: 99%
“…Outlines and models for test reporting have been offered (Hammond & Allen, 1953;Klopfer, 1960;Lodge, 1953;Sargent, 1951;Taylor & Teicher, 1946). The need to tailor the report to the particular context in which the testing referral was made has been affirmed by Sargent (1951), and the issue of portraying the patient in behavioral terms rather than in abstractions has been discussed by her in the same paper and recommended by others (Garfield, Heine, & Leventhal, 1954). The consumer's motives for asking or not asking for tests have been well delineated by Brody (1959).…”
Section: Discussionmentioning
confidence: 99%
“…While he will be interested in the level of performance as reflected in the IQ, this aspect alone can be viewed as being within the traditional psychometric approach. Computing a score and interpreting it in the light of a table of norms requires little clinical judgment, for as Holt (1961) has observed, clinical judgment is exclusive of the combination of quantitative data or scores. The test becomes a clinical tool or method when the clinician becomes a part of the analytical and interpretive process.…”
Section: Description Of the Clinical Methodsmentioning
confidence: 99%
“…The theoretical approach of Doliard and Miller (1950) is one outstanding example. Even such a staunch experimentalist as Eysenck (1961) has based a moderate amount of his work on theories developed by Jung. Further, a number of important concepts which are in wide use today in psychology-e.g., anxiety, displacement, repression, projection, etc.-are largely derived from clinical investigations and formulations about personality.…”
Section: The Clinical Methods and Personality Theorymentioning
confidence: 99%